Factors associated with umbilical cord clamping in term newborns - Juliana Karine Rodrigues Strada; Leticia Becker Vieira; Helga Geremias Gouveia; Thais Betti; Wiliam Wegner; Cecília Drebes Pedron (SciELO, 2022)
ABSTRACT OBJECTIVE: To identify factors associated with umbilical cord clamping in term newborns and to compare the recording of clamping time in the medical record with what was observed. METHOD: Cross-sectional study, with 300 mothers-infants, in a university hospital. Clamping time and medical records were observed, and a structured questionnaire was applied to postpartum women for sociodemographic variables. Bivariate analysis, multivariate Poisson Regression model, and Kappa concordance test were performed. RESULTS: The percentage of late/optimal clamping observed was 53.7%. The associated factors were skin-to-skin contact in the delivery room (PR = 0.76; 0.61-0.95; p = 0.014), position of the newborn below the vaginal canal (PR = 2.6; CI95%: 1.66-4.07; p < 0.001), position of the newborn at the vaginal level (PR = 2.03; CI95%: 1.5-2.75; p < 0.001), and need for newborn resuscitation in the delivery room (PR = 1.42; CI95%; 1.16-1.73; p = 0.001). Kappa concordance level of the professionals, records compared to the observation was: nurse 0.47, obstetrician 0.59, and pediatrician 0.86. CONCLUSION: the identification of associated factors and the comparison between recording and observing the clamping time can help in the planning and implementation of improvements for adherence to good practices at birth.